PEMBELAJARAN BERBASIS LEARNER AUTONOMY TOPIK GELOMBANG CAHAYA UNTUK MELATIHKAN KETERAMPILAN PROSES SAINS - Siti Nor Fatmah; Mastuang Mastuang; Abdul Salam (FKIP ULM, 2018)
Abstract. The low level of science process skills (KPS) of students has an impact on the difficulty to understand physics learning. For this reason, a development research which aimed to produce and describe the feasibility of learning devices based on learner autonomy that are able to train science process skills was carried out. The research used a development model of ADDIE. The research subjects were 26 eleventh graders of science class-3 (class XI IPA-3) of Public Senior High School (SMAN) 6 Banjarmasin. Data collection techniques were carried out by observation and tests. Technical data analysis was carried out in quantitative and qualitative descriptive ways. The results showed that the learning devices developed were: (1) valid according to academician’s assessment with very good categories, (2) practical according to the implementation of lesson plan (RPP) with very good category, (3) Effective according to the gain score achieved with moderate category, and (4) result in students’ Science Process Skills (KPS) achievement with skilled category. Thus, it can be concluded that the learning devices based on learner autonomy to train science process skills developed are feasible to be used in learning. Keywords: learner autonomy, science process skills. Abstrak. Rendahnya keterampilan proses sains (KPS) peserta didik berdampak pada kesulitan memahami pembelajaran fisika. Untuk itu dilakukan penelitian pengembangan yang bertujuan untuk menghasilkan perangkat pembelajaran berbasis learner autonomy yang mampu melatihkan keterampilan proses sains, sekaligus mendeskripsikan kelayakannya. Model pengembangan yang digunakan adalah model ADDIE. Subjek uji coba penelitian ini adalah 26 peserta didik kelas XI IPA 3 SMAN 6 Banjarmasin. Teknik pengumpulan data dilakukan dengan observasi dan tes. Teknis analisis data dilakukan secara deskriptif kuantitatif dan kualitatif. Hasil penelitian menunjukkan bahwa perangkat pembelajaran yang dikembangkan: (1) valid berdasarkan penilaian akademisi dengan kategori sangat baik, (2) praktis berdasarkan keterlaksanaan RPP yang berkategori sangat baik, (3) Efektif berdasarkan perolehan gain skor yang berkategori sedang, dan (4) Pencapaian KPS siswa berkategori terampil. Dengan demikian dapat disimpulkan bahwa perangkat pembelajaran berbasis learner autonomy untuk melatihkan keterampilan proses sains layak digunakan dalam pembelajaran. Kata kunci: Learner Autonomy, Keterampilan Proses Sains.